2018
DOI: 10.1371/journal.pone.0196047
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dengue outbreaks in Mexico based on entomological, meteorological and demographic data

Abstract: Dengue virus has shown a complex pattern of transmission across Latin America over the last two decades. In an attempt to explain the permanence of the disease in regions subjected to drought seasons lasting over six months, various hypotheses have been proposed. These include transovarial transmission, forest reservoirs and asymptomatic human virus carriers. Dengue virus is endemic in Mexico, a country in which half of the population is seropositive. Seropositivity is a risk factor for Dengue Hemorrhagic Feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…2.2 Population density in village factor (PDVF) indicates the number of people per square kilometre. This model of human population density predicted dengue outbreak 8 , 26 because dengue virus transmission occurs between humans and mosquitoes. High population density is associated with increasing dengue incidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 Population density in village factor (PDVF) indicates the number of people per square kilometre. This model of human population density predicted dengue outbreak 8 , 26 because dengue virus transmission occurs between humans and mosquitoes. High population density is associated with increasing dengue incidence.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 1.8 billion live in South-East Asia and Western Pacific regions, and 500 000 dengue cases require hospitalization yearly, with a death rate of 2.5%. 1 - 3 The main risk factors of dengue include rainfall, temperature, 4 , 5 mosquito density, 6 density of people, 7 , 8 dengue types, 5 non-specific treatment, 1 , 2 no effective dengue vaccine, 5 , 9 ineffective drugs, 5 human immunity, 10 people’s movement across areas, 11 , 12 population density, 13 attitude toward dengue prevention, 14 , 15 and occupation. 12 Interventions to address dengue problems combine community mobilization, entomological methods, and chemical and biological controls.…”
Section: Introductionmentioning
confidence: 99%
“…require optimum temperatures ranging between 15–35 °C to fully develop and survive. Moreover, studies by Chen & Hsieh [52] in Taiwan and Sánchez-González et al [53] in Mexico indicated that the highest risk of dengue transmission generally occurs at a temperature of 28 °C. There is compelling evidence that this optimal temperature reduced gonotrophic cycles for Aedes mosquitoes, prolonging of the mosquitoes’ life expectancy, shortening of the extrinsic incubation periods of arboviruses, and facilitating the dispersal of vectors across broader geographical areas [13, 14, 51], which could potentially lead to a greater probability of dengue transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The same occurs with the number of infection recoveries, the TNSEs and the NSCEs. The rain season is modeled as a 4-month period sine function, were the temperature changes from 25 °C to 30 °C, which cross the optimal transmission temperature ranging between 27-28 °C, as we already showed in our previous work (23). The parameters used to calculate the model are show at Table 1.…”
Section: Methodsmentioning
confidence: 94%